МОДЕЛЬ ПЛАНУВАННЯ РОБОТИ АКТИВНОГО СПОЖИВАЧА НА РОЗДРІБНОМУ РИНКУ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ - Блінов, І.В.; Парус, Є.В.; Артемчук, В.О. (Інститут електродинаміки НАН України, Київ, 2026)
The publication is devoted to the description of the mathematical model for solving the problem of planning schedules of purchase and sale of electric energy by a prosumer. The main goal of optimization is to maximize the benefit as the difference between revenues from the sale of electric energy and costs for the purchase of electric energy. The objective function and the system of equations of electric energy balances are given. Models for controlling the directions of energy flows in individual nodes of the local electric energy system of a prosumer are formalized. The mathematical model for controlling the level of filling of the energy storage unit as the main means of balancing energy flows in the microgrid is detailed. The features of the formation of optimal schedules of purchase/sale of electric energy, as well as schedules for regulating the modes of the energy storage unit under conditions of different volumes of electric energy release from the source of unregulated generation are investigated. References 19, figures 3.